Identification of Cd-resistant microorganisms from heavy metal-contaminated soil and its potential in promoting the growth and Cd accumulation of bermudagrass - Xie, Yan; Bu, Heshen; Feng, Qijia; Wassie, Misganaw; Amee, Maurice; Jiang, Ying; Bi, Yufang; Hu, Longxing; Chen, Liang (Environmental research, 2021)
Phytoremediation has been increasingly used as a green technology for the remediation of heavy metal contaminated soils. Microorganisms could enhance phytoremediation efficiency by solubilizing heavy metal and improve plant growth by producing phytohormones in the heavy metal contaminated soils. In this study, we investigated the abundance and composition of soil microbial communities in heavy metal contaminated soils. Furthermore, we identified a Cd-resistant fungal strain Penicillium janthinellum ZZ-2 and assessed its potential in improving plant growth, Cd accumulation and Cd tolerance in bermudagrass. The results indicated that long-term heavy metal pollution decreased microbial biomass and activity by inhibiting microbial community diversity, but did not significantly affect community composition. Mainly, the relative abundance of some specific bacterial and fungal taxa, such as Actinobacteria, Chloroflexi, Bacteroidetes, Ascomycota and Basidiomycota, changes under metal pollution. Furthermore, at genus level, certain microbial taxa, such as Pseudonocardiaceae, AD3, Latescibacteria, Apiotrichum and Paraboeremia, only exist in polluted soil. One Cd-resistant fungus ZZ-2 was isolated and identified as Penicillium janthinellum. Further characterization revealed that ZZ-2 had a greater capacity for Cd2+ absorption, produced indole-3-acid (IAA), and facilitated plant growth in the presence of Cd. Interestingly, ZZ-2 inoculation significantly increased Cd uptake in the stem and root of bermudagrass. Thus, ZZ-2 could improve plant growth under Cd stress by reducing Cd-toxicity, increasing Cd uptake and producing IAA. This study suggests a novel fungus-assisted phytoremediation approach to alleviate Cd toxicity in heavy metals contaminated soils. •Soil microbes as indicators of soil pollution with heavy metals.•Heavy metal contamination inhibited the microbial activity.•A new Cd-resistant strain was isolated and identified as Penicillium janthinellum.•Penicillium janthinellum ZZ-2 promoted the plant growth and Cd uptake•ZZ-2 might be used to improve the efficiency of metal extraction from soil.